Konstruksi Kewenangan Majelis Permusyawaratan Rakyat dalam Memberikan Keterangan pada Perkara Pengujian Undang-Undang di Mahkamah Konstitusi - M. Adib Akmal Hamdi; Xavier Nugraha; Gio Arjuna Putra (Universitas Widya Gama Malang, 2023)
In the light of this background, the focus of this article is on 3 (three) issues namely: the MPR's authority to interpret the constitution, the construction of ius constitutum providing statements by the MPR in reviewing laws in the Constitutional Court, and the reconstruction of the ius constituendum model of providing information on requests for review of laws law in the Constitutional Court. This article is a legal research with a reform-oriented research type with statutory, case, and conceptual approaches. Based on this research, several things were found, namely: (1) the People’s Consultative Assembly has the authority to interpret the constitution based on Article 3 paragraph (1) of the 1945 Constitution of the Republic of Indonesia; (2) the construction of the ius constitutum position of the People’s Consultative Assembly in the petition for review of a law at the Constitutional Court is derogated by the exclusion of the MPR as giving explanation in Constitutional Court Law Number 6 Year 2005; (3) at the ius constituendum level, the involvement of the People’s Consultative Assembly in carrying out originalism interpretation of the constitution can be realized through the provision of explanation in a tripartite manner, namely the Government and/or the DPR as legislators and the People’s Consultative Assembly as the framers of the constitution. This article provides recommendations for the need to amend the provisions of the Constitutional Court's procedural law, so as to provide space for substantive participation for the MPR in providing an interpretation of its constitution.